2017
DOI: 10.1103/physrevb.96.235105
|View full text |Cite
|
Sign up to set email alerts
|

Massive fermions with low mobility in antiferromagnet orthorhombic CuMnAs single crystals

Abstract: We report the physical properties of orthorhombic o-CuMnAs single crystal, which is predicted to be a topological Dirac semimetal with magnetic ground state and inversion symmetry broken. o-CuMnAs exhibits an antiferromagnetic transition with TN ∼ 312 K. Further characterizations of magnetic properties suggest that the AFM order may be canted with the spin orientation in the bc plane. Small isotropic MR and linearly field-dependent Hall resistivity with positive slope indicate that single hole-type carries wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…We concluded that this magnetic structure breaks the S 2z symmetry, leading to the disappearance of Dirac fermions. This is consistent with a following study on CuMnAs single crystals based on the argument that the easy axis is in the ab plane [13]. Our first-principles calculations show that this magnetic order can support spin-polarized states, a much sought after property for spintronics.…”
Section: Introductionsupporting
confidence: 91%
“…We concluded that this magnetic structure breaks the S 2z symmetry, leading to the disappearance of Dirac fermions. This is consistent with a following study on CuMnAs single crystals based on the argument that the easy axis is in the ab plane [13]. Our first-principles calculations show that this magnetic order can support spin-polarized states, a much sought after property for spintronics.…”
Section: Introductionsupporting
confidence: 91%
“…[37]. We note, that weakly temperature-dependent behavior with negative slope above T N was observed for polycrystalline orthorhombic CuMnAs [28].…”
Section: Electrical Transport With Spin Fluctuationsmentioning
confidence: 52%
“…All momentum space integrals were carried out on a 350 × 350 × 350 grid in the first Brillouin zone, where convergence was verified when incremental increases in the grid size amounted to less than 5% difference in the integrated value. The anti-ferromagnetic spin configuration of the M n atoms was implemented in accordance with experimental findings on the commensurate AFM (c-AFM) structure in orthorhombic CuMnAs [60,61], with spins oriented along the b-axis. We recover the experimental result that the c-AFM order breaks the screw symmetry S 2z , while also breaking the R y nonsymmorphic reflection symmetry.…”
Section: Methodsmentioning
confidence: 76%
“…Therefore, PT materials are ideal candidates to investigate the AGA through their intrinsic nonlinear conductivity. On top of that, the only two remaining Hall contributions, σ dr and σ gr , behave differently under permutation of the spatial indices, so that the Drude contribution σ dr can be subtracted away, for example, by taking a combination σ We have calculated σ (2) and σ gr for the orthorohmbic phase of CuMnAs, which is antiferromagnetic and breaks P and T but preserves PT [60,61]. As shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation